An Assessment of Training Practices in the Small and Medium-Sized Enterprises in Kedah and Perlis - Zuhaidah, Salleh (2004)
Human resource management practices such as training can assist organizations improve their effectiveness. More importantIy, small and medium-sized enterprises (SMEs) need training to help them increase their skills and knowledge in order to become competitive. However, the review of the small business literature revealed that scant research attention has been given to investigate the training practices in SMEs as a means of improving their effectiveness and competitiveness, particularly in the Malaysian context. This study attempted to address this issue. The empirical information resulted from analyzing the data collected from 41 SMEs in the states of Kedah and Perlis suggests the following findings: 1. the SMEs needed training in various areas; 2. the SMEs perceived training as important; 3. the SMEs adopted different methods of training; 4. the SMEs used different types of training; 5. the training provided in the SMEs was suitable to the firms; and 6. the employees of the SMEs attended limited numbers of training in the form of short courses.